Proposal of an objective formula-based model for equitable ranking of veterinary colleges - Gogal, Robert M.; Holladay, Steven David (Frontiers in Veterinary Science, 2025)
IntroductionWe suggest an objective ranking formula that has wide national and international application. The new formula is presented with U.S. Colleges of Veterinary Medicine as an example. Methods used by ranking agencies differ, as do the ranks they generate. In some instances, relatively narrow information is collected from a limited number of polled contributors, raising questions about strength and validity of the generated ranks.MethodsA new formula-based weighted model for ranking of veterinary colleges is proposed. Numbers fed into the formula parameters, for instance teaching hospital case load, faculty number and research expenditures, derive from real and measurable qualities of each college and drive an objective final ranking score for each veterinary college. This formula is designed to be readily modified within and beyond the veterinary profession.ResultsThe new ranking system works from calculations that are straightforward and transparent with little room for subjective interpretation. It is designed to provide a rigorous and defendable institutional rank for all veterinary colleges.DiscussionThe new ranking system is designed to be readily adaptable within veterinary colleges as the profession changes, as well as to academic institutions with focuses other than veterinary medicine. The goal is to provide a new model that is useful for objective comparisons.